2006
DOI: 10.1210/en.2006-0216
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblasts Provide a Suitable Microenvironment for the Action of Receptor Activator of Nuclear Factor-κB Ligand

Abstract: Deficiency of osteoprotegerin (OPG), a soluble decoy receptor for receptor activator of nuclear factor-kappaB ligand (RANKL), in mice induces osteoporosis caused by enhanced bone resorption. Serum concentrations of RANKL are extremely high in OPG-deficient (OPG(-/-)) mice, suggesting that circulating RANKL is involved in osteoclastogenesis. RANKL(-/-) mice exhibit osteopetrosis, with the absence of osteoclasts. We examined the requirements for osteoclastogenesis using OPG(-/-) mice, RANKL(-/-) mice, and a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…We previously reported that osteoclasts were generated in bone in response to an injection of RANKL in RANKL 2/2 mice, as they were in wild-type mice (Yamamoto et al, 2006). Osteoclasts were not observed in the soft tissues around the bone in RANKLinjected RANKL 2/2 mice, indicating that the expression of RANKL is not involved in determining the correct site for osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…We previously reported that osteoclasts were generated in bone in response to an injection of RANKL in RANKL 2/2 mice, as they were in wild-type mice (Yamamoto et al, 2006). Osteoclasts were not observed in the soft tissues around the bone in RANKLinjected RANKL 2/2 mice, indicating that the expression of RANKL is not involved in determining the correct site for osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…When RANKL was injected into these RANKL À / À mice, osteoclasts appeared in BMP-2-containing disks but not in the control disk. 51 These results suggested that some QOPs circulated in the blood and settled in the bone (Figure 6a). The distribution of QOPs was similar to that of ALP þ osteoblasts in RANKL À / À mice, 49 suggesting that ALP þ bone-forming osteoblasts are somehow involved in homing of QOPs to the bone.…”
Section: Circulating Osteoclast Precursorsmentioning
confidence: 89%
“…RNA of all cells was extracted from osteoblasts following the method of Yamamoto et al [26] and complementary DNA was synthesized from the RNA using a reverse transcription (RT) device (ReverTra Ace, Toyobo, Osaka, Japan).…”
Section: Quantification Of Calciummentioning
confidence: 99%